Resolusi Konflik Keluarga Berbasis Local Wisdom (Reaktualisasi Filosofi Masyarakat Sulawesi Utara Torang Samua Basudara) - Ahmad Rajafi (Program Studi Hukum Keluarga Islam, 2016)
The term “ torang samua basudara” was the slogan of the community in North Sulawesi in order to keep social harmony and peace in the North Sulawesi. In the context of family law, the idea of “torang samua basudara” implemented in micro to solve family conflicts in the form of divorce so that it can leave a further conflicts, especially for family members, so it takes a formula constructive to actualize the ideas “torang samua basudara” which implies the decline of divorce rate in North Sulawesi. Through the symbol “torang samua basudara” it can built up through value meaning as a process, not as a result. As a process, the value or the idea of “torang samua basudara” expose the openness of thought and communication between couples (husband and wife) more intensively so that family problems will be more easily solved and conflict resolution will present first, before the presentconflict toward divorce